Chemical Ligation and Isotope Labeling to Locate Dynamic Effects during Catalysis by Dihydrofolate Reductase1. (16th June 2015) - Luk, Louis Y. P.; Ruiz‐Pernía, J. Javier; Adesina, Aduragbemi S.; Loveridge, E. Joel; Tuñón, Iñaki; Moliner, Vincent; Allemann, Rudolf K.
Abstract Chemical ligation has been used to alter motions in specific regions of dihydrofolate reductase from E. coli and to investigate the effects of localized motional changes on enzyme catalysis. Two isotopic hybrids were prepared; one with the mobile N‐terminal segment containing heavy isotopes (2H, 13C, 15N) and the remainder of the protein with natural isotopic abundance, and the other one with only the C‐terminal segment isotopically labeled. Kinetic investigations indicated that isotopic substitution of the N‐terminal segment affected only a physical step of catalysis, whereas the enzyme chemistry was affected by protein motions from the C‐terminal segment. QM/MM studies support the idea that dynamic effects on catalysis mostly originate from the C‐terminal segment. The use of isotope hybrids provides insights into the microscopic mechanism of dynamic coupling, which is difficult to obtain with other studies, and helps define the dynamic networks of intramolecular interactions central to enzyme catalysis.